RAMBU PEMBELAJARAN DANPENILAIAN SASTRA ANAK - Burhan Nurgiyantoro (LPMPP Universitas Negeri Yogyakarta, 2007)
Efforts to develop children's personality to the optimum should be made viavarious aspectsmlife, one of which is children's literature. Such literature is atpresent believed to be able to significantly.contribute to the shaping of children'spersonality. Therefore,it needs to be given its proper place in the learning andlearning achievement evaluation activities at school, which is in line with what isstated in the curriculum now in use, i.e., KTSP (short for Kurikulum Tingkat SatuanPerfdidikan, which means the Curriculum at the Level of Educational Unit), forelementary school in referring tothe school subject Pendidikan Bahasa Indonesia(which means Education in the Indonesian Language).In running classes of children's literature for children of pre